The Beginnings of Greek Allegoresis - Domaradzki, Mikołaj (My University, 2017)
The present article examines the question of who was the rst to have allegorically interpreted Homer. The fragmentary and indirect character of the extant testimonies on the beginnings of allegoresis makes it very dif cult to adjudicate between the candidates Theagenes of Rhegium and Pherecydes of Syros. This paper argues that while the surviving testimonies suggest that The- agenes was the rst allegorist of Homer, Pherecydes’ appropria- tion of mythology is likely to have created premises for allegorical interpretation of poetry. Thus, it is argued that both Theagenes and Pherecydes be considered as important gures in the emer- gence of allegoresis.